Synthesizing Common Procedures for Developing Publicity Materials: Integrating Theory and Practice in Global Professional Communication - Novawan, Adriadi; Alvarez-Tosalem, Susan Mila; Aswandi, Aswandi; Ismailia, Titik; Zuhro, Cholimatus (P3M Politeknik Negeri Jember, 2024)
The development and dissemination of effective publicity materials are essential for professional communicators in public relations, communication, and marketing in this digital and globalized world. These materials, encompassing various media formats, play a crucial role in conveying messages, shaping public perceptions, and engaging target audiences. With the rapid development of digital technology and the need for integrated communication strategies, creating persuasive, ethical, and transparent materials has become increasingly important. This study aims to identify and synthesize common procedures for the development of publicity materials through a systematic literature review (SLR) of 77 highly cited international references in public relations, marketing, communication, and media. Key stages of the methodology include defining research questions, identifying and selecting relevant literature, extracting and analysing data, and summarizing common procedures. The findings reveal essential elements such as audience analysis, objectives-setting, message development, communication channel selection, and effectiveness appraisal. This study also highlights the importance of cultural sensitivity, two-way communication, and the integration of technology in developing effective publicity materials. The study concludes with recommendations for future research, including the development of comprehensive models or frameworks that can further enhance the creation of impactful publicity materials in diverse contexts.